Proposal of a preventive maintenance plan for central air conditioning (Revista Científica Estelí, 2015)
It includes the job done in the central air conditioners of the hospital San Juan de Dios in the city of Estelí, such as the diagnostics of the equipment and the routine of maintenance, measurements with respect to the hours worked by each machine and by the specialized technician in his work, the costs and benefits that would correspond to a change in the maintenance philosophy from a corrective form to a preventive one. These studies defined the necessary basis for a proposal of a preventive maintenance plan that will guarantee the useful life of the central airs, this will allow a defined function of these analyzes and control as to the quality of service perceived by the population.Keywords: Maintenance, Preventive, plants.